Al-Ahmad and His Place in Iran’s Subjective Narration - مجتبی دماوندی; فواد مولودی (تاریخ ادبیات)
The present article is the analysis of subjective narration in Jalal Al-Ahmad’s short stories “Someone Else’s Child” and “American Husband.” In the first part, we have dealt with theoretical issues about subjective narration and the conditions of its realization, in order to show that this kind of narration is simultaneously realized in form and content, or in aesthetic or epistemological systems. The conscious author, in order to create exulted subjective narrative, presents the “language” of the narrative and the five components of “time”, “place”, “plot”, “narrator’s voice”, and “character” in a modernist and subjective structure, and it is the manner of processing these components which produces multiple semantic and epistemic layers and creates a distance from pre-modern dogmatism. Al-Ahmad was one of the first Iranian writers who tried to realize subjective narration in Persian prose, dealing with this type of narration in some of his works. In the present study, with regard to the above-mentioned theoretical framework, we have analyzed Al-Ahmad’s first and last attempt in this realm, that is, “Someone Else’s Child” (1327) and “American Husband” (1350), in the attempt to measure the amount of his success in the modern aesthetics of subjective narration, and gauge the compatibility of his thought with the epistemology of this kind of narration.